Event-by-event fluctuations of the mean transverse momentum in 40, 80, and 158 A GeV/c Pb-Au collisions: CERES collaboration - Adamová, Dagmar; Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Glässel, Peter; Dubitzky, Wilrid; Milošević, Jovan; Richter, Michael; Specht, Hans Joachim; Stachel, Johanna; et al. (Arxiv, 2003)
Measurements of event-by-event fluctuations of the mean transverse momentum in Pb-Au collisions at 40, 80, and 158 A GeV/c are presented. A significant excess of mean p_T fluctuations at mid-rapidity is observed over the expectation from statistically independent particle emission. The results are somewhat smaller than recent measurements at RHIC. A possible non-monotonic behaviour of the mean p_T fluctuations as function of collision energy, which may have indicated that the system has passed the critical point of the QCD phase diagram in the range of mu_B under investigation, has not been observed. The centrality dependence of mean p_T fluctuations in Pb-Au is consistent with an extrapolation from pp collisions assuming that the non-statistical fluctuations scale with multiplicity. The results are compared to calculations by the RQMD and UrQMD event generators.